2013
DOI: 10.1021/ja400225n
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Gold Nanoparticles into Bilayer Structures via Adaptive Surface Chemistry

Abstract: We describe the spontaneous incorporation of amphiphilic gold nanoparticles (Au NPs) into the walls of surfactant vesicles. Au NPs were functionalized with mixed monolayers of hydrophilic (deprotonated mercaptoundecanoic acid, MUA) and hydrophobic (octadecanethiol, ODT) ligands, which are known to redistribute dynamically on the NP surface in response to changes in the local environment. When Au NPs are mixed with preformed surfactant vesicles, the hydrophobic ODT ligands on the NP surface interact favorably w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 30 publications
6
87
0
Order By: Relevance
“…For example, the strong similarity of the AuNP-bilayer fusion process to the pre-stalk transition state for vesicle-vesicle fusion may allow these AuNPs to be used to probe the properties of fusogenic systems. Furthermore, the demonstration of strong thermodynamic forces associated with such insertion provides further evidence that such a process may explain recent experimental observations of non-disruptive association between AuNPs and bilayers 24,25,30,31 . Finally, the fusogenic properties of these AuNPs may present new opportunities for devising novel strategies for endosomal escape, drug delivery, controlled biodistribution and so on, all important research avenues for enhancing treatments based on nanomedicine.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…For example, the strong similarity of the AuNP-bilayer fusion process to the pre-stalk transition state for vesicle-vesicle fusion may allow these AuNPs to be used to probe the properties of fusogenic systems. Furthermore, the demonstration of strong thermodynamic forces associated with such insertion provides further evidence that such a process may explain recent experimental observations of non-disruptive association between AuNPs and bilayers 24,25,30,31 . Finally, the fusogenic properties of these AuNPs may present new opportunities for devising novel strategies for endosomal escape, drug delivery, controlled biodistribution and so on, all important research avenues for enhancing treatments based on nanomedicine.…”
Section: Discussionsupporting
confidence: 54%
“…The thermodynamic driving force for insertion was the hydrophobic effect: the amphiphilic particle surfaces could eliminate waterexposed hydrophobic surface area by inserting into the hydrophobic bilayer core while retaining hydrophilic end groups in aqueous solution by 'snorkelling' 28,29 . Other experimental systems have found such complexation as well 30,31 . Although these previous studies have elucidated the thermodynamics of nanoparticle insertion into lipid bilayers 24,25,32 , the detailed kinetics of the insertion process are still unclear.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…18 Experimental studies of similar monolayer-protected NPs have observed behavior consistent with bilayer insertion in several other systems. 2224 Because bilayer insertion requires charged ligand end groups to cross the bilayer, these observations again indicate that charged groups may cross the bilayer more rapidly than anticipated when grafted to a complex material system, although the molecular details of this process are unknown. Understanding how such grafting affects the rate of charge transport could be of great use in drug delivery applications by revealing design guidelines for synthetic materials capable of ferrying water-soluble therapeutic compounds or genetic material across the cell membrane.…”
Section: Introductionmentioning
confidence: 97%
“…For example, embedded metal nanoparticles larger than ca. 6.5 nm may disrupt the lipid bilayer, resulting in micelle formation ( 21 , 28 , 30 , 31 ). The attachment of the nanoparticles onto the surface of the outer lipid often leads to leakage of the liposome structure ( 32 ).…”
Section: Introductionmentioning
confidence: 99%